Key Drivers of Relationship Commitment in Supply Chain Management: Insights from Thailand’s Manufacturing Industry - Sawaengdee, Siriwadee; Zhu , Bing (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2025)
Relationship commitment is a vital asset in today’s dynamic business, as it cultivates connections among different parties and enhances a company’s performance. This study explores how relationship commitment can be enhanced and strengthened, improving supply chain management performance within the Thai manufacturing industry. Based on in-depth interviews with nine executives in the Thai manufacturing sector, trust was found essential. Furthermore, trust promotes integration and collaboration within partnerships. The findings offer effective strategies for enhancing relationship commitment in supply chains, highlighting the crucial role of trust in achieving operational efficiency and success.